Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3390/ijms24032194
|View full text |Cite
|
Sign up to set email alerts
|

A Straightforward Cytometry-Based Protocol for the Comprehensive Analysis of the Inflammatory Valve Infiltrate in Aortic Stenosis

Abstract: Aortic stenosis (AS) is a frequent cardiac disease in old individuals, characterized by valvular calcification, fibrosis, and inflammation. Recent studies suggest that AS is an active inflammatory atherosclerotic-like process. Particularly, it has been suggested that several immune cell types, present in the valve infiltrate, contribute to its degeneration and to the progression toward stenosis. Furthermore, the infiltrating T cell subpopulations mainly consist of oligoclonal expansions, probably specific for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…Cells were thawed at 37 °C and immediately processed downstream following established protocols 16 . Briefly, cells were counted and suspended at 1x10 6 /mL in sodium-azide free DPBS, with BD Horizon™ Fixable Viability Stain (1:1000) at room temperature for 15 minutes protected from light.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Cells were thawed at 37 °C and immediately processed downstream following established protocols 16 . Briefly, cells were counted and suspended at 1x10 6 /mL in sodium-azide free DPBS, with BD Horizon™ Fixable Viability Stain (1:1000) at room temperature for 15 minutes protected from light.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…This phenomenon has been observed in diseases such as coronary atherosclerosis 13 and atrial fibrillation 14 . There is increasing evidence that erythrocytes, leukocytes and platelets are activated in AS 1, 15, 16 . In addition, other evidence showed that ECs were activated in AS 17 .…”
Section: Introductionmentioning
confidence: 99%